2023
DOI: 10.1680/jensu.21.00071
|View full text |Cite
|
Sign up to set email alerts
|

Development of sustainable prefabricated housing system by small-scale experimental model

Abstract: Utilisation of unused industrial wastes and need for rapid volumetric construction led to the evolution of sustainable prefabricated housing elements, particularly for urban slums. An agro-industrial by-product as raw material and waste expanded polystyrene beads as the insulation material are chosen to develop a lightweight prefabricated construction element. This bio-ash is used as a partial replacement, 20% and 10% for the fine aggregates to prepare concrete and lightweight mix respectively. A small-scale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The unused ash was acquired and tested for its suitability as a construction material. Various characterization tests have proved its applicability as fine aggregate and was partially replaced [15,33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unused ash was acquired and tested for its suitability as a construction material. Various characterization tests have proved its applicability as fine aggregate and was partially replaced [15,33].…”
Section: Methodsmentioning
confidence: 99%
“…Buildings 2023, 13, x FOR PEER REVIEW 4 of 17 material. Various characterization tests have proved its applicability as fine aggregate and was partially replaced [15,33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials of CFA-based end products were designed as per the Codal standards. The optimal mix trials were concluded for both concrete (Table 1) and LW mix (Table 2) [41], with a target of being superior to traditional construction products. Their respective physico-mechanical along with functional properties were compared to conventional products, as shown in Table 3.…”
Section: Design and Testingmentioning
confidence: 99%
“…The prefabrication technique was selected for the building of the model house, and the housing plan was scaled down to one-third of its original size. Precast structural elements (Figure 6) and prefabricated walling panels (Figure 7) were cast and cured as per the Codal standards [41]. The model house (Figure 8) was assembled with these elements in a shadow-free region at the Civil Engineering Department, Visvesvaraya National Institute of Technology, Nagpur, India.…”
Section: Building Of a Small-scale Model Housementioning
confidence: 99%